2014
DOI: 10.7554/elife.01808
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide-mediated oligomerization of a defensin induces cell lysis

Abstract: Cationic antimicrobial peptides (CAPs) such as defensins are ubiquitously found innate immune molecules that often exhibit broad activity against microbial pathogens and mammalian tumor cells. Many CAPs act at the plasma membrane of cells leading to membrane destabilization and permeabilization. In this study, we describe a novel cell lysis mechanism for fungal and tumor cells by the plant defensin NaD1 that acts via direct binding to the plasma membrane phospholipid phosphatidylinositol 4,5-bisphosphate (PIP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
247
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(267 citation statements)
references
References 77 publications
(125 reference statements)
12
247
1
Order By: Relevance
“…Similar PI(4,5)P 2 -binding mechanism was also described for the tomato defensin TPP3, which binds specifically to PI(4,5)P 2 and shares the conserved cationic grip binding pocket as NaD1 to mediate cell lysis. 70 It should be noted that the cationic loop region identified as the PA binding site in MtDef4, is conserved among many plant defensins 119,120 and interestingly, the equivalent region (between β2 and β3 strands) was also found to be the PI (4,5)P 2 binding site for both NaD1 and TPP3, 69,70 indicating that this region is functionally conserved to bind phospholipid. Intriguingly, the ability of these plant innate defense molecules to induce membrane permeabilization via binding to inner membrane PI(4,5)P 2 and forming oligomers resembles the aforementioned PI(4,5)P 2 -dependent targeting and oligomerization by MLKL in mammalian cells undergoing necroptosis.…”
Section: Pathogenic Entry Via the Host Extracellular Phospholipid Codementioning
confidence: 96%
See 4 more Smart Citations
“…Similar PI(4,5)P 2 -binding mechanism was also described for the tomato defensin TPP3, which binds specifically to PI(4,5)P 2 and shares the conserved cationic grip binding pocket as NaD1 to mediate cell lysis. 70 It should be noted that the cationic loop region identified as the PA binding site in MtDef4, is conserved among many plant defensins 119,120 and interestingly, the equivalent region (between β2 and β3 strands) was also found to be the PI (4,5)P 2 binding site for both NaD1 and TPP3, 69,70 indicating that this region is functionally conserved to bind phospholipid. Intriguingly, the ability of these plant innate defense molecules to induce membrane permeabilization via binding to inner membrane PI(4,5)P 2 and forming oligomers resembles the aforementioned PI(4,5)P 2 -dependent targeting and oligomerization by MLKL in mammalian cells undergoing necroptosis.…”
Section: Pathogenic Entry Via the Host Extracellular Phospholipid Codementioning
confidence: 96%
“…49 Recently, it was demonstrated that the plant defensin NaD1, a CAP isolated from the ornamental tobacco Nicotiana alata, can selectively induce membrane lysis (primary necrosis) of mammalian tumor cells through binding PI(4,5)P 2 at the inner leaflet of the plasma membrane at low micromolar concentrations. 69 Although how NaD1 enters the tumor cell and gains access to the intracellular phospholipid code is unclear, the ability of NaD1 to form a multimeric complex with the phosphatidylinositol head group of PI(4,5)P 2 suggests the possibility of NaD1 acting as a phospholipid detector that can mask the cellular function of PI(4,5)P 2 , discussed further below. 69 More recently, the closely related tomato defensin, TPP3, was also shown to induce PI(4,5)P 2 -mediated tumor cell permeabilization via a similar mechanism.…”
Section: Alteration Of the Phospholipid Code During Tumor Progressionmentioning
confidence: 99%
See 3 more Smart Citations